Money Income and Expenditure of Major Regional Organization of the Communist Party in 1955-1985 (on Materials of Sverdlovsk Regional Party Committee) - V. N. Mamyachenkov (Научный диалог)
The article is devoted to the subject insufficiently developed in the national historiography. The study was conducted on materials of the State archive of the Sverdlovsk region and the Center of documentation of public organizations of Sverdlovsk region. The topic urgency is determined by its high relevance for the social sciences, especially history, sociology and political science. Scientific novelty of the work is seen in the fact that the new material discovered by the author in these archives is introduced into usage. It is stated that the analysis of money income and expenditure of the ruling party of the former USSR is an important area of research in the field of national history, and the annual financial reports of the regional party structures represent a unique source of information. It is argued that in the USSR at the level of state secrets any information about the income of the party functionaries and their privileges intentionally suppressed, as well as the information on the financial activities of the Communist party in general. It is proved that the Communist party completely disposed the finances not only belonged to it, but also the resources of the whole country using them in its own purposes, for example, to finance the deficit of budget of the party. It is declared that the revenue and expenditure budgetary activities of regional party organizations had their own interesting characteristics, studying of which allows to expand the framework of our understanding of their functioning. It is emphasized that the party budget of regional committee of the party was rather arbitrary category and had primarily control and audit function.